2017
DOI: 10.3389/fncel.2017.00172
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem-Cell Transplantation Promotes Functional Improvement Associated with CNTF-STAT3 Activation after Hemi-Sectioned Spinal Cord Injury in Tree Shrews

Abstract: Hemi-sectioned spinal cord injury (hSCI) can lead to spastic paralysis on the injured side, as well as flaccid paralysis on the contralateral side, which can negatively affect a patient’s daily life. Stem-cell therapy may offer an effective treatment option for individuals with hSCI. To examine the role of bone marrow mesenchymal stem cells (BMSCs) transplantation on hSCI and explore related mechanisms in the tree shrews, here, we created a model of hSCI by inducing injury at the tenth thoracic vertebra (T10).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Consistent with our results, previous studies demonstrated that intrathecal delivery of BMSCs can relieve neuropathic pain and that the analgesic effect of BMSCs persists for at least 14 days [34,35]. Mesenchymal stem-cell therapy, such as BMSCs treatment, has been considered a potentially successful approach for treating various diseases including neuropathic pain [37,46], spinal cord injury [47,48], Alzheimer's disease [49,50], stroke [51,52], and lung injury [53,54]. BMSCs were the earliest and the most widely studied MSCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, previous studies demonstrated that intrathecal delivery of BMSCs can relieve neuropathic pain and that the analgesic effect of BMSCs persists for at least 14 days [34,35]. Mesenchymal stem-cell therapy, such as BMSCs treatment, has been considered a potentially successful approach for treating various diseases including neuropathic pain [37,46], spinal cord injury [47,48], Alzheimer's disease [49,50], stroke [51,52], and lung injury [53,54]. BMSCs were the earliest and the most widely studied MSCs in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that BMMSCs could induce neural cell repair by secreting neurotrophic factors, promoting axonal regeneration leading to functional improvement following spinal cord injury [ 7 9 ]. In this study, immunohistochemistry showed that on day 7 after surgery, the transplanted BMMSCs could significantly reduce neuronal necrosis in the spinal cord of the ischemic segments, and increase the number of normal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMMSCs) have the advantages of ease of availability, a reduced risk of immune rejection, multipotential cell differentiation, and multiple transplantation pathways, which make them ideal tissue engineering and transplant stem cells, which can also be used in arterial and aortic transplantation [ 6 ]. Transplanted BMMSCs have been shown to secrete a variety of neurotrophic factors, which exert a synergistic neuroprotective effect with exogenous neurotrophic factors [ 7 9 ]. In a previous study, BMMSCs have been shown to express and secrete ciliary neurotrophic factor (CNTF) in vitro [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implantation of BMSCs has shown to have regenerative and immunomodulative properties that help to prevent the GS formation [91]. Furthermore, these cells are able to regulate CNTF-STAT3 signal transduction which reduces tissue scarring, inflammatory responses, and apoptosis [92]. Okuda et al reported that BMSC sheets suppress the GS and provide a positive environment for axonal regeneration, causing changes in reactive astrocyte morphology [93].…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%